Characterization of bacteria colonizing the mucosal layer of the gastrointestinal tract of Atlantic salmon farmed in a warm water region - Reid, Chantelle E.; Taylor, Richard S.; Bissett, Andrew; Nowak, Barbara F.; Bowman, John P. (Frontiers in Microbiology, 2025)
Atlantic salmon (Salmo salar) farmed in seawater in Tasmania (lutruwita) can experience temperatures close to their thermotolerance limit during summer. Gut microbiome data from eight successive annual surveys and a specific survey of GI tract mucosa and digesta bacterial cross-sectional distributions indicated that members of the genus Aliivibrio, Vibrio, and an unclassified Mycoplasmoidaceae are the main colonizers of the gut mucosal layer in Tasmanian farmed salmon. Peak abundance levels were reached 7–8 months after the transfer of smolt to sea cages from hatcheries. This corresponds to late summer, with the transfer of hatchery smolt occurring in winter. Salmon Aliivibrio isolates comprise three novel non-bioluminescent species. Along with other Aliivibrio species, these species have genes in common required for host colonization and biofilm formation, and also include species- and strain-level dependent features. Two of the novel Aliivibrio species surprisingly possessed genes for cytolethal distending toxin, while the more predominant species lacked any known virulence genes. The overall observations suggest a restricted group of species actively colonizes the mucosal layer of Atlantic salmon farmed in Tasmania, and that this process is strongly influenced by environmental temperature.